2018
DOI: 10.1002/prca.201700085
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ‐Based Proteomic Analysis Reveals Protein Profile in Plasma from Children with Autism

Abstract: These above described proteins are found involved in different pathways that have previously been linked to the pathophysiology of autism spectrum disorders (ASDs). The results strongly support that focal adhesions, acting cytoskeleton, cell adhesion, motility and migration, synaptogenesis, and complement system are involved in the pathogenesis of autism, and highlight the important role of platelet function in the pathophysiology of autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 91 publications
(107 reference statements)
2
39
5
Order By: Relevance
“…Fewer proteomics studies on ASD have been published than those based on other disciplines, such as genomics or transcriptomics. Many of them rely on post-mortem brain tissues [ 50 , 51 , 52 ], serum [ 53 , 54 , 55 , 56 ], plasma [ 57 , 58 , 59 ], urine [ 63 ], saliva [ 60 , 61 , 62 ] direct samples or lymphoblastoid cell lines [ 64 ] ( Table 1 ).…”
Section: Translational and Clinical Proteomicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fewer proteomics studies on ASD have been published than those based on other disciplines, such as genomics or transcriptomics. Many of them rely on post-mortem brain tissues [ 50 , 51 , 52 ], serum [ 53 , 54 , 55 , 56 ], plasma [ 57 , 58 , 59 ], urine [ 63 ], saliva [ 60 , 61 , 62 ] direct samples or lymphoblastoid cell lines [ 64 ] ( Table 1 ).…”
Section: Translational and Clinical Proteomicsmentioning
confidence: 99%
“…Recently, Shen et al used the iTRAQ-based proteomics approach to compare plasma protein profiles of ASD compared with healthy subjects. They identified 24 differentially expressed proteins expressed in different pathways associated with ASDs [ 59 ] ( Table 1 ). This evidence supports the thesis that synapsis growth, the complement system, cytoskeleton-related activities and cell adhesion are all involved in ASD.…”
Section: Translational and Clinical Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, C4b binds to the complement protein FIGURE 1 | Complement activation pathways and the activity or expression of their individual components (either protein or mRNA) in schizophrenia and autism spectrum disorder (ASD). ↑ red, increased protein activity or expression in blood from patients; ↓ red, decreased protein activity or expression in blood from patients; ↑ blue, increased RNA expression in brain tissues from patients; ↓ blue, decreased RNA expression in brain tissues from patients (Spivak et al, 1989(Spivak et al, , 1993Warren et al, 1994;Wong et al, 1996;Maes et al, 1997;Shcherbakova et al, 1999;Hakobyan et al, 2005;Mayilyan et al, 2006;Corbett et al, 2007;Boyajyan et al, 2010;Momeni et al, 2012;Nardone et al, 2014;Li et al, 2016;Sekar et al, 2016;Fagan et al, 2017;Shen et al, 2018). The Figure does not distinguish between strong and weak evidence.…”
Section: Complement System Activation: a Backgroundmentioning
confidence: 99%
“…Genetic association studies have reported that the complement C4B gene null allele has increased frequency in patients with ASD compared to control individuals (Warren et al, 1991;Odell et al, 2005;Mostafa and Shehab, 2010) and, accordingly, a significant decrease in the plasma levels of C4B protein was observed in ASD patients (Warren et al, 1994; Figure 1). On the other hand, proteomic analyses have suggested that the levels of other complement system proteins, such as C1q, C3, and C5, are elevated in plasma from patients with ASD (Corbett et al, 2007;Shen et al, 2018; Figure 1). In addition, a significantly increased activity of CFI, a negative regulatory component of the alternative pathway responsible for cleavage and inactivation of C3b and C4b, has been observed in plasma from ASD patients (Momeni et al, 2012).…”
Section: Complement In Autism Spectrum Disorder and In Rett Syndromementioning
confidence: 99%